Community Medicine as A Career Option! How Is It Perceived by Medical Students? - Manish Kumar Singh; Arvind Kumar Singh (Medsci Publications, 2013)
Aim: This study was conducted to assess possible reasons for medical students opting for or shying away from Community medicine as a career option.   Methodology: A cross-sectional study was done among MBBS students, interns and fresh medical graduates at a medical college in Uttar Pradesh. Study tool was an open-ended questionnaire in first phase and a pre-tested structured questionnaire in second phase. Results: About 15.7% students opted for Community medicine as a career option. Male students and students not having a doctor in their family showed higher preference. Community medicine cannot bring in "name/fame equivalent to other clinical subjects" ranked topmost in rejection criteria, followed by "lack of personal satisfaction", "recognition in society" and "lack of information on future career prospects". A statistically significant difference was also observed for the above cited reasons. Conclusions: Fear of not being able to earn name/fame, recognition in society and job satisfaction in comparison to other clinical subjects along with lack of information regarding future career prospects seem to be the most important causes for rejection of Community medicine as a career option.